2013
DOI: 10.1517/17425247.2013.790887
|View full text |Cite
|
Sign up to set email alerts
|

Direct nose to brain drug deliveryviaintegrated nerve pathways bypassing the blood–brain barrier: an excellent platform for brain targeting

Abstract: Direct nose to brain drug delivery system is a practical, safe, non-invasive and convenient form of formulation strategy and could be viewed as an excellent alternative approach to conventional dosage forms. Existence of a direct transport route from the nasal cavity to the brain, bypassing the BBB, would offer an exciting mode of delivering neurotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
217
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(220 citation statements)
references
References 73 publications
0
217
0
3
Order By: Relevance
“…The extracellular transportation is a rapid process which is permitted to occur only few minutes within olfactory cells (39). In contrast, the intracellular transport mechanism is a slow process and lasts for over several hours by axonal transportation (40).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular transportation is a rapid process which is permitted to occur only few minutes within olfactory cells (39). In contrast, the intracellular transport mechanism is a slow process and lasts for over several hours by axonal transportation (40).…”
Section: Discussionmentioning
confidence: 99%
“…Nasal cavity irradiation is convenient and causes no injury. It is reported that drugs absorbed by nasal mucosa can be easily transported to the brain, 32 and intranasal route is the alternative route to parenteral administration. 33 Nasal cavity irradiation helps CNT go across the BBB and brings better central analgesic effects.…”
Section: Analgesic Effects Of the Cnt Nanocapsulesmentioning
confidence: 99%
“…Thus, the trigeminal pathway, which is often overlooked by the researchers, can be an important direct pathway of drug delivery to the brain. [16,17,18,19] Three branches of the trigeminal nerve (ophthalmic division, maxillary division, and mandibular division) merge at the trigeminal ganglion, enter the CNS in the pons, and terminate in the spinal trigeminal nuclei in the brainstem. Therefore, cross-talk between the trigeminal and olfactory routes of brain drug delivery is possible.…”
Section: Pathways For Reaching the Drug To Brain After Intranasal Admmentioning
confidence: 99%